THE LEGAL RESPONSIBILITY OF A PRIVATE MILITARY COMPANY (PMC) IN AN INTERNATIONAL ARMED CONFLICT UNDER HUMANITARIAN LAW - Lalu Nahudatu Akbariman; Zunnuraeni; Guna Nugraha, Lalu (Mataram Journal of International Law, 2024)
The existence of Private Military Company (PMC) in most contemporary armed conflicts as a non-participant has raised the legal question regarding the status and legal standing of PMC. This research aims to analyze the legal position and determine the legal responsibility of PMC in international armed conflicts according to Humanitarian Law. The research employed a normative legal research method, utilizing international treaties, national legislation, and international customary law as the basis. The findings reveal that, under international law, the PMC is not a party legally authorized to engage in armed conflicts. The legal responsibility of the PMC for crimes in violation of international humanitarian law and human rights can be attributed to both civil responsibility and criminal responsibility for war crimes, based on the principle of corporate criminal responsibility. However, the non-recognition of PMC as subjects of international law means that PMCs cannot be held criminally liable under international law. Therefore, the existence of humanitarian law in the national legal system paves the way for the criminal prosecution of PMC as a company.